Perjanjian Penyerahan Jaminan Sebagai Penyelesaian Hutang Di Hadapan Notaris - Maryana Siregar, Agustina (Recital Review, 2021)
The notary makes an agreement regarding AYDA (repossessed assets) which aims to authorize the bank represented by one of its directors.The existence of an agreement on the delivery of collateral as a debt settlement before a notary that is emerging in banking practice is certainly expected to provide legal certainty for both the debtor, the owner of the collateral and the bank as the creditor. However, in the laws and regulations in Indonesia there is no regulation that specifically regulates the agreement on the delivery of collateral as debt settlement.This thesis is a descriptive research and the type of research used is a normative juridical study. Study on Verdict Number: 24/Pdt.G/2019/PN.Pti regarding the deed of guarantee delivery agreement between the creditor and the debtor indicates that the agreement does not meet the legal requirements as an agreement. This became evident in March 2016 when the debtor experienced financial difficulties so that the payment of debt installments was delayed.Then there are six deeds issued by a notary in which the six deeds are defects of will or defects of agreement due to abuse of circumstances.This stems from the existence of procedures that are not carried out by creditors, namely the absence of a warning letter regarding delays.Thus, the debtor as the aggrieved party files a lawsuit as a form of legal certainty against the object of the dispute that is his. Â Keywords: AYDA, deed of sale & purchase, mortgage right